已知实数x,y,满足x²+y²-2x+4y+5=0,试求x,y的值 已知x(x+1)(x+2)(x+3)+1=25求x²+3x的值

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/20 21:28:14
已知实数x,y,满足x²+y²-2x+4y+5=0,试求x,y的值 已知x(x+1)(x+2)(x+3)+1=25求x²+3x的值

已知实数x,y,满足x²+y²-2x+4y+5=0,试求x,y的值 已知x(x+1)(x+2)(x+3)+1=25求x²+3x的值
已知实数x,y,满足x²+y²-2x+4y+5=0,试求x,y的值 已知x(x+1)(x+2)(x+3)+1=25求x²+3x的值

已知实数x,y,满足x²+y²-2x+4y+5=0,试求x,y的值 已知x(x+1)(x+2)(x+3)+1=25求x²+3x的值
x^2+y^2-2x+4y+5=0
x^2-2x+1+y^2+4y+4=0
(x-1)^2+(y+2)^2=0
(x-1)^2=0.(y+2)^2=0
x=1,y=-2
x(x+1)(x+2)(x+3)+1=25
x(x+1)(x+2)(x+3)-24=0
x(x+3)(x+1)(x+2)-24=0
(x^2+3x)(x^2+3x+2)-24=0
(x^2+3x)^2+2(x^2+3x)-24=0
(x^2+3x+6)(x^2+3x-4)=0
因为(x^2+3x+6)>0
所以(x^2+3x-4)=0
x^2+3x=4

已知实数x,y,满足x²+y²-2x+4y+5=0,试求x,y的值
(x-1)^2+(y+2)^2=0
x=1,y=-2
已知x(x+1)(x+2)(x+3)+1=25求x²+3x的值
(x^2+3x)(x^2+3x+2)+1=25
((x^2+3x)^2+2(x^2+3x)-24=0
x^2+3x=-6或4
因为x^2+3x+6=0无实根,所以舍x^2+3x=-6
故x^2+3x=4

x²+y²-2x+4y+5=0
x²-2x+1+y²+4y+4=0
(x-1)²+(y+2)²=0
∵(x-1)²≥0,(y+2)²≥0
∴x-1=0,y+2=0
即x=1,y=-2
(x+1)(x+2)x(x+3)+1=25
(x²+3x+2)(x&#...

全部展开

x²+y²-2x+4y+5=0
x²-2x+1+y²+4y+4=0
(x-1)²+(y+2)²=0
∵(x-1)²≥0,(y+2)²≥0
∴x-1=0,y+2=0
即x=1,y=-2
(x+1)(x+2)x(x+3)+1=25
(x²+3x+2)(x²+3x)+1=25
(x²+3x)²+2(x²+3x)-24=0
(x²+3x+6)(x²+3x-4)=0
即x²+3x=-6或x²+3x=4

收起

x=y=1
4

(x-1)=0且y+2=0即x=1 y=-2

1)x²+y²-2x+4y+5=0
(x-1)^2+(y+2)^2=0
x=1,y=-2
2)x(x+1)(x+2)(x+3)+1=25
x(x+3)(x^2+3x+2)+1=25
x(x+3)[x(x+3)+2]+1=25
设t=x(x+3)
t^2+2t-24=0
t=4 or t=-6
即 x^2+3x=4 or -6